PENGARUH FREKUENSI DAN APLIKASI INSEKTISIDA ABAMECTIN TERHADAP KELIMPAHAN POPULASI DAN PERSENTASE SERANGAN LALAT PENGOROK DAUN LIRIOMYZA SPP (DIPTERA: AGROMYSIDAE) - Arfan Arfan; Lisa Indriani Bangkele; Hasmari Noer (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2018)
Effect of Frequency and Application of Abamectin Insecticides on Population Abundance and Attack Level of Leafminer Liriomyza, spp. (Diptera: Agromysidae) is one of the main pests on the Lembah Palu red onion, where this pest is relatively new in the Palu Valley. The aim of the study was to examine the effect of frequency and application of insecticides on population abundance, and the attack rate of L. chinensis (Diptera: Agromyzidae) on the Lembah Palu red onion plant under applied and unapplied insecticide. The treatment of abamectin insecticide was applied once a week with a concentration of 1 ml of formulation per liter of water, beginning at the age of 2 MST and ending at 7 MST. The results showed that there were 2 species of Liriomyza, spp associated with Palu valley red onion i.e. Liriomyza chinensis and Liriomyza sativae. This research found that the application of Abamectin insecticides significantly affected population development and the percentage of Liriomyza, spp. on the lembah Palu red onion.